The Influence of Using Animated Videos to Improve Students Vocabulary and Pronunciation in English Language Learning - Revia Febriyanita. M; Nuzulul Isna (Universitas Islam Negeri Palopo, 2025)
This study aims to determine the effect of animated videos in improving students' vocabulary and pronunciation in English language learning. The subjects in this study were grade fifth students totaling 36 elementary school students who followed the learning process with animated video media as an intervention. The method used was a quasi-experiment with pre-test and post-test design. The data were analyzed using the Wilcoxon Signed Ranks Test. The results showed a significant increase in students' vocabulary and pronunciation skills after the intervention. The statistical test showed a significant difference between the pre-test and post-test results of students' vocabulary and pronunciation skills. These findings reinforce the theory that audiovisual media, particularly animated videos, can help improve students' memory, context understanding, and learning motivation. Therefore, the use of animated videos as learning media is highly recommended to improve students' English proficiency in an effective and fun way. Keywords: animated video, vocabulary, pronunciation, English language learning, elementary school students